Taxonomic notes species of Macromitrium (Musci: Orthotrichaceae) with multistratose laminae, with three new synonyms - Li, Dandan; He, Lin; Yang, Jun; Yu, Jing; Guo, Shuiliang (Phytotaxa, 2025)
Twenty-one species of Macromitrium Brid. (Orthotrichaceae) with multistratose laminae were taxonomically evaluated based on their type specimens and authentic history specimens. Macromitrium onraedtii Bizot. was found conspecific with M. serpens (Bruch. ex Hook. & Grev.) Brid., and M. bifasciculare Müll. Hal ex Dusén and M. bifasciculatum Müll. Hal were conspecific with M. saddleanum Besch. ex Müll. Hal. The circumscription of M. saddleanum was revised. A key to eighteen presently-recognized Macromitrium species with multistratose laminae was also given.